Nilai-Nilai Al-Kulliyatul Al-Khamsah dalam Mencegah Pergaulan Bebas dan Zina pada Fase Baligh - Abid Tania Rahmawati; Muwahidah Nurhasanah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Premarital sex and promiscuity have become significant issues among high school students. This qualitative study, using a phenomenological approach, investigates the implementation of al-Kulliyatul al-Khamsah (the five fundamental principles of Islam) in preventing these behaviors. The study focuses on: 1) the extent to which these principles (preserving religion, life, intellect, lineage, and wealth) are incorporated into the daily lives of adolescents at SMA Negeri 1 Widodaren; 2) the correlation between the application of these principles and the prevalence of premarital sex and promiscuity; and 3) the challenges faced in promoting these principles within this context. Data was collected through interviews with students, parents, and teachers, as well as classroom observations over one semester. Findings indicate that the application of al-Kulliyatul al-Khamsah is effective in mitigating these issues. Keywords: promiscuity, fornication, puberty, fundamental principles of Islam